Neuropsychological Functions of μ- and δ-Opioid Systems. (26th December 2013) - Polunina, Anna G.; Bryun, Evgeny A.
Abstract : Brain opioid innervation is involved in many pathophysiological processes related to drug addiction. The main idea of the present review is that μ -/ δ -opioid innervation is an intrinsic component of the motor/approach behavior network, which is activated synergetically with dopaminergic mesocorticolimbic network. Contribution of opioid innervation to the motor/approach behavior processing includes generation of positive emotions and inhibition of pain and stress reactions in order that the individual would be able to reach the vital goal. We cite the neuroanatomical data which showed that motor subcortical nuclei contain the most abundant opioid innervation and its activation is an obligatory component of positive emotions. In the majority of life situations, motor/approach behavior network concomitantly activates pain/stress control opioid network. Intensive cognitive activity induces activation of opioid innervation as well, and both enhancing and impairing effects of opioid agonists on cognitive functioning were demonstrated. Overall, the functioning of endogenous opioid networks may be summarized as following: NO physical/cognitive activity = NO positive emotions plus NO pain/stress control. We suppose that contemporary findings concerning neuropsychological functions of endogenous opioid system explain many controversial issues in neuropsychiatric conditions predisposing to drug addiction and neurological mechanisms of opioid addiction.